Maintenance tegafur-plus-uracil after adjuvant concurrent chemoradiotherapy may improve outcome for resected oral cavity squamous cell carcinoma with extranodal extension - Huang, Pei-Wei; Lin, Chien-Yu; Lee, Li-Yu; Hsieh, Chia-Hsun; Hsu, Cheng-Lung; Liau, Chi-Ting; Fan, Kang-Hsing; Huang, Shiang-Fu; Liao, Chun-Ta; Chang, Tung-Chieh; Wang, Hung-Ming (Frontiers in Oncology, 2022)
Objectives: To evaluate whether tegafur-uracil maintenance (UFTm) following post-operation adjuvant cisplatin-based concurrent chemoradiotherapy (CCRT) may reduce distant metastasis in patients with resected oral cavity squamous cell carcinoma (OSCC) with pathologic extranodal extension (pENE+). Methods: A retrospective comparison was conducted between two cohorts of patients with resected pENE+ OSCC who completed adjuvant CCRT between March 2015 and December 2017, including one cohort of a phase II trial using UFTm and a trial-eligible but off protocol cohort without using UFTm (non-UFTm) after their adjuvant CCRT. The UFTm trial enrolled patients without relapse within 2 months after the end of adjuvant CCRT and administered UFT 400 mg/day for 1 year. Kaplan-Meier methods estimated the actuarial rate of distant metastasis-free (DMF), locoregional control (LRC), event-free survival (EFS), and overall survival (OS). Results: A total of 103 patients were included in this study, 64 patients in UFTm and 39 patients in non-UFTm. Severe adverse events in UFTm included grade 3 anemia (n=1, 1.6%) and grade 3 mucositis (n=1, 1.6%). A total of 40 (62.5%) patients completed the full course of UFTm, while the remaining terminated UFTm earlier due to disease relapse (n=14, 21.8%), poor compliance (n= 9, 14.1%), and adverse event (n=1, 1.6%). The median (range) follow-up time of surviving patients was 43 (22-65) months. The outcomes compared between UFTm and non-UFTm were OS (hazard ratio [HR] 0.31 [95% CI: 0.17-0.57], p<0·001), EFS (0.45, [0.25-0.82], 0.009), LRC (0.45 [0.19-1.05], 0.067), and DMF (0.47 [0.24-0.95], 0.035). Multivariable analysis, adjusted for UFTm, Charlson comorbidity index score 1-3, site of tongue, and number of ENE+ LN≧4, confirmed better OS (0.29, [0.16-0.54], <0.001) and EFS (0.47, [0.26-0.85], 0.012) in favor of UFTm over non-UFTm. The 2-year DM rate was 25.8% in UFTm and 44.2% in non-UFTm. For relapsed patients in UFTm vs. non-UFTm, the rate of metastasectomy for oligometastasis was 53% vs. 6%, and the OS was 21.0 (95% CI: 17.8-24.1) months vs. 11.0 (9.1-12.8) months (p < 0.001), respectively. Conclusions: UFTm may improve the dismal outcomes of the resected pENE+ OSCC. Further investigations are needed to confirm our observations.